2021
DOI: 10.21601/ijese/9605
|View full text |Cite
|
Sign up to set email alerts
|

Situation of Environmental Education in Senior High School Programs in Indonesia: Perspectives from the Teachers of Palembang

Abstract: Environmental literacy helps to address key challenges in providing sustainable development for the developing third world countries. This can be qualified based on the active practice of promoting environmental awareness inside the classroom and innovative curriculum change among many educational systems. To provide a glimpse of the current situation of environmental education at the senior high school level, this pioneering qualitative research study based on grounded theory was conducted for Indonesia by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 32 publications
1
19
0
2
Order By: Relevance
“…Studies on environmental education (EE) in the Indonesian context found that the notion of EE in the country's previous curriculum-Curriculum 2013-is extremely limited 49,50 . There was no mandatory implementation of EE at the primary and secondary levels 51 . This might be attributed to the serious lack of political will, leadership, and interest in environmental matters from the government 50 Several climate change studies have investigated the knowledge of climate change among Indonesian students 49,52 .…”
Section: Climate Change Education In the Indonesian Contextmentioning
confidence: 99%
“…Studies on environmental education (EE) in the Indonesian context found that the notion of EE in the country's previous curriculum-Curriculum 2013-is extremely limited 49,50 . There was no mandatory implementation of EE at the primary and secondary levels 51 . This might be attributed to the serious lack of political will, leadership, and interest in environmental matters from the government 50 Several climate change studies have investigated the knowledge of climate change among Indonesian students 49,52 .…”
Section: Climate Change Education In the Indonesian Contextmentioning
confidence: 99%
“…Estudios internacionales considerados previos a esta investigación como Dagamac (2021) develan como este autor administró una encuesta cuidadosamente construida donde fueron seleccionados mediante una técnica de muestreo aleatorio simple. Utilizando la prueba Tau-b de Kendall y la medida de correlación de rango Gamma (G o γ), se midió la asociación entre la participación de los medios en línea relacionada con problemas ambientales y el comportamiento fuera de línea proambiental.…”
Section: Referentes: Una Aproximaciónunclassified
“…This is because every activity in which humans interact with the environment and the excessive use of environmental resources during these interactions causes environmental degradation (Eba, 2020). The fact that the young generation will inherit the harsh consequences of environmental degradation caused by economic development is inevitable unless no measures are taken for a solution (Darmawan & Dagamac, 2021). Therefore, all kinds of activities done by people without thinking cause a negative effect on the environment and these negative effects on the environment increase incrementally every day (García-González, García-Palencia & Sánchez-Ondoño, 2021).…”
Section: Evaluation Of Prospective Teachers' Attitudes Towards Sustai...mentioning
confidence: 99%